Incidence of intracardiac thrombus formation prior to electrical cardioversion in respect to the mode of oral anticoagulation. (15th February 2018) - Schaeffer, Benjamin; Rüden, Lea; Salzbrunn, Tim; Pinnschmidt, Hans O.; Akbulak, Ruken Özge; Moser, Julia Magdalena; Jularic, Mario; Meyer, Christian; Eickholt, Christian; Sultan, Arian; Lüker, Jakob; Steven, Daniel; et al.
Abstract: Aims: To evaluate the incidence of newly diagnosed intracardiac thrombi (ICT) in respect to the mode of OAC in patients undergoing cardioversion (CV). Methods and results: We prospectively assessed transesophageal echocardiography (TEE) and OAC therapy prior to CV in AF patients with ≥48‐hour duration scheduled for CV. A total of 60 first‐time ICT (4.7%) were diagnosed in 1, 286 TEE, with highest rate in patients without OAC (9.6% vs. OAC 4.1%, P = 0.009) and an apparently lower rate in nonvitamin K antagonist anticoagulants (NOAC) therapy compared to vitamin K antagonist (VKA) (2.5% vs. 5.3%, P = 0.02). VKA therapy control 4 weeks prior to CV was overall average (time in therapeutic range 60%) and patients showed more frequently clinical characteristics and TEE parameters associated with risk for ICT. Even among patients with effective OAC therapy (uninterrupted NOAC and VKA therapy with international normalized ratio (INR) ≥2.0 for 3 weeks), ICT occurred in 2.7%, but with no difference between both groups (P = 0.22). There was no difference between different types of NOAC. Independent predictors for ICT were history of embolism, hypertension, BMI, absence of OAC, renal function, reduced atrial appendage flow, and presence of spontaneous echo contrast. Conclusion: NOAC therapy seems favorable in the overall prevention of ICT, although this is likely to be caused by suboptimal VKA therapy control and differences in the overall health status between VKA and NOAC patients. ICT occurred even with effective OAC therapy suggesting individual TEE‐guided cardioversion in patients at risk.